Nurse in the Prison Service and coping with occupational stress. - Kotarba, Agnieszka; Borowiak, Ewa (Nursing Problems / Problemy Pielęgniarstwa, 2016)
Introduction. The penitentiary nurses reveal the highest intensity of stress among officers working in direct contact with the prisoners. The constructive coping with occupational stress has a major impact on the welfare of nurses and quality of care for the charges. Aim. Identifying the dominant style of coping with occupational stress and the identification of factors that determine it in the group of nurses penitentiary. Material and methods. The study of 50 nurses - prison officers of one of the penitentiaries and detention centers in Łódź. In this study has been used: original questionnaire; Questionnaire Coping with stressful situations (CISS). Results and conclusions. In the study group the highest average was observed for the task style for the lowest emotional style. The differences between the averages for styles of coping with stress were statistically significant in the case of task and avoidance style. The value of PTS affects both - the corps (F = 4.6; p = 0.049) and subjective evaluation of work under the stress (F = 10.72, p = 0.002). There were no statistically significant correlation between the scales SSA and SSE and demographic variables and associated with the work environment. The style of coping with stress is a significant personal resource used in work environment of nurse - a prison officer. However, in the group of penitentiary nurses the dominant style of coping with occupational stress has been not identified. The tendency to prefer not adaptive style of coping with difficult situations is related to the corpus and the subjective perception of stressful environment. The obtained results indicate need for further research in order to identify those who require assistance in using adaptive style of coping with occupational stress.